GR-AMRVAC code applications: accretion onto compact objects, boson stars versus black holes. (7th July 2016) - Meliani, Z; Grandclément, P; Casse, F; Vincent, F H; Straub, O; Dauvergne, F
Abstract: In the close vicinity of a compact object strong gravity imprints its signature onto matter. Systems that contain at least one compact object are observed to exhibit extreme physical properties and typically emit highly energetic radiation. The nature of the compact objects that produce the strongest gravitational fields is to date not settled. General relativistic numerical simulations of fluid dynamics around black holes, neutron stars, and other compact objects such as boson stars (BSs) may give invaluable insights into this fundamental question. In order to study the behavior of fluid in the strong gravity regime of an arbitrary compact object we develop a new general relativistic hydrodynamics code. To this end we extend the existing versatile adaptive mesh refinement code MPI-AMRVAC into a general relativistic hydrodynamics framework and adapt it for the use of numerically given spacetime metrics. In the present article we study accretion flows in the vicinity of various types of BSs whose numerical metrics are calculated by the KADATH spectral solver library. We design specific tests to check the reliability of any code intending to study BSs and compare the solutions with those obtained in the context of Schwarzschild black holes. We perform the first ever general relativistic hydrodynamical simulations of gas accretion by a BS. The behavior of matter at small distances from the center of a BS differs notably from the black hole case. In particular we demonstrate that in the context of Bondi spherical accretion the mass accretion rate onto non-rotating BSs remains constant whereas it increases for Schwarzschild black holes. We also address the scenario of non-spherical accretion onto BSs and show that this may trigger mass ejection from the interior of the BS. This striking feature opens the door to forthcoming investigations regarding accretion-ejection flows around such types of compact objects.